Formulasi Kebijakan Rechterlijke Pardon dalam Perspektif Pembaharuan Hukum Pidana di Indonesia - Uut Rahayuningsih; Wardhana, Yudha Kusuma; Nadianti, Jenita; Noor, Abdillah Ramadhan (Amsir Law Journal, 2026)
This study aims to analyze the concept of judicial pardon (Rechterlijk Pardon) as a key foundation for criminal law reform in Indonesia, which is transitioning from a colonial-era Criminal Code paradigm toward a more humanistic and context-sensitive sentencing system. Employing a normative legal research method, the article examines statutory provisions particularly those contained in the Draft/New Indonesian Criminal Code as well as relevant doctrinal writings and scholarly literature concerning the authority of judges to refrain from imposing punishment, even when the defendant has been legally proven guilty, provided that specific conditions are met, such as the minor nature of the offence, the personal circumstances of the offender, and compelling considerations of justice and humanity. The findings demonstrate that judicial pardon functions as a short-term alternative to imprisonment, a judicial corrective to the rigid application of the legality principle, and a “safety valve” to prevent decisions that are formally lawful but substantively unjust, thereby strengthening a shift in penal orientation toward restoration, protection of human dignity, and the reduction of over‑criminalization. From a policy perspective, the institutionalization of judicial pardon within Indonesia’s criminal law reform agenda is consistent with the values of Pancasila and the principle of punishment as an ultimum remedium, and it opens the way for a more balanced sentencing framework that integrates legal certainty, utility, and substantive justice in line with contemporary United Nations standards on humane and proportionate criminal justice